A Comparative Analysis of Sore Throat and Fever as Presenting Symptoms of COVID-19 in a Tertiary care Hospital at Taxila - Farhan Ahmed, Muhammad Aslam Khan, Kashif Iqbal, Zainab Zaffar, Mirza Nasheed Baig, Muhammad Noaman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The Corona virus disease 2019 (COVID-19) pandemic exerted a substantial global health impact, including within Pakistan. This study aimed to compare the frequency of upper respiratory symptoms, specifically sore throat and fever, among individuals hospitalized with COVID-19 at Heavy Industries Taxila (HIT) Hospital between July and December 2022. The influence of vaccination status on symptom presentation was also explored. Objective: To compare sore throat and fever among adult COVID-19 patients at HIT Hospital and to explore potential associations between patient characteristics and symptom presentation. Study Design: Descriptive cross-sectional study Methodolgy: A cross-sectional study was conducted following ethical approval (HITEC-IRB-16-2021). A total of 151 hospitalized COVID-19 patients were enrolled. Data on upper respiratory symptoms, vaccination history, and clinical outcomes were collected using a structured questionnaire. Results: The study population comprised 151 individuals (60 males, 91 females) aged 3 to 77 years (mean: 36.46). Sore throat and fever were reported by 72.8% and 73.5% of patients, respectively. Conclusion: Sore throat and fever emerged as common presenting symptoms among hospitalized COVID-19 patients at HIT Hospital. Further research is necessary to elucidate the association between vaccination status and the manifestation of these upper respiratory symptoms. Keywords: COVID-19, fever, hospital, Pakistan, sore throat